LITHUANIAN LEARNERS’ ENGLISH: BRITISH OR AMERICAN? - Bikelienė, Lina (Verbum, 2015)
The aim of the research was to examine Lithuanian learners’ conscious and subconscious preference for one of the two major varieties of the English language: British and American. Three aspects – spelling, the choice of lexical items, and prepositions – were selected for the study. The data on these aspects as well as on Lithuanian learners’ overt preference and explicit choice of the variety were obtained from a questionnaire completed by 124 students of all the study programmes at the Institute of Foreign Languages. Since spelling is believed to be the most indicative of varietal differences, it was seen as the key aspect of the present research. Six systemic spelling groups were analysed in five corpora of Lithuanian learners’ English: AFK1, LICLE-VU, LICLE-VDU, CALE-SUM-LIT and CALE-RPA-LIT. The questionnaire- and corpora-based research revealed an insignificant preference of British English norms. The overtly expressed preference for British English correlates with the year of study. This finding is consistent with the studies that reported on direct correlation between the language level and the preference for British English. The questionnaire revealed the tendency to use British English even when it was not the students’ choice. The conflicting results of the students’ ideas of which variety they use and real usage are indicative of the lack of learners’ awareness concerning varietal differences. This can also be supported by the fact that there was not a single respondent whose use of the norms characteristic of one variety was consistent. The corpora-derived data highlighted possible institutionally-induced differences since LICLE-VU and LICLE-VDU revealed the opposite tendencies, the former favouring British, while the latter – American spelling. The analysis of separate spelling groups, however, indicated inconsistent choice of varietal norms among them. The scope of the present research was limited in terms of the number of respondents and the size of the questionnaire. The results, therefore, should be treated as tentative and should be tested on a larger sample of respondents.
Keywords: learner corpora; varieties of English; spelling; prepositions